Activation of membrane protein-tyrosine phosphatase involving cAMP- and Ca2+/phospholipid-dependent protein kinases. - Brautigan, D L (1991)
Essential to signal transduction are mechanisms of "cross-talk" to coordinate different pathways. This study shows that stimulation of serine/threonine protein kinases activates protein-tyrosine phosphatase (PTPase; protein-tyrosine-phosphate phosphohydrolase, EC 3.1.3.48). More than 95% of intracellular PTPase was in the particulate fraction of various cell lines and was extracted with detergent as a 150-kDa complex that contained a 55-kDa catalytic subunit. The complex was activated by protease digestion, which changed its substrate specificity coincident with reduction in size. The complex was dissociated by treatment of the membrane fraction with 3 M LiBr. Treatment of intact cells with isoproterenol, forskolin, or cAMP analogues to stimulate cAMP-dependent protein kinase (PKA) or with phorbol ester or dioctanoylglycerol to stimulate Ca2+/phospholipid-dependent protein kinase (PKC) produced activation of membrane PTPase complex without a change in its size. Inhibition of protein-serine/threonine phosphatases with okadaic acid or fluoride also resulted in activation of the membrane PTPase. These results support a model for regulation of PTPase by phosphorylation and dephosphorylation of serine/threonine residues in a regulatory component complexed with the 55-kDa PTPase catalytic subunit. This mechanism may be important in regulating sensitivity to extracellular signals transduced via tyrosine phosphorylation and in the synchronization of events during the cell cycle.